Alkali-free glass
Patent Information
- Application Number
- JP2024203033
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-02-05
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0048】 本発明は、ガラス基板が反るなどのガラス基板の変形を抑制でき、成型性に優れ、製造設備への負担が低いことに加えて、結晶成長速度が低く、生産性および品質が更に優れるガラスを提供できる。
Smart Images

Figure 2025024182000001 
Figure 2025024182000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an alkali-free glass suitable as substrate glass for various displays, photomasks, electronic device supports, information recording media, planar antennas, light control laminates, vehicle window glass, acoustic diaphragms, and the like. [Background technology]
[0002] Conventionally, glass plates (glass substrates) for various displays, photomasks, electronic device supports, and information recording media, particularly glass used for glass plates on whose surfaces a thin film of metal or oxide is formed, have been required to have the following properties (1) to (4): (1) In the case where the glass contains an alkali metal oxide, the alkali metal ions diffuse into the thin film and deteriorate the film properties of the thin film, so the glass must be substantially free of alkali metal ions. (2) The glass sheet must have a high strain point so as to minimize deformation of the glass sheet and shrinkage (compaction) associated with stabilization of the glass structure when the glass sheet is exposed to high temperatures during the thin film formation process.
[0003] (3) It has sufficient chemical durability against various chemicals used in semiconductor formation. In particular, SiO x and SiN x It must be durable against buffered hydrofluoric acid (BHF: a mixture of hydrofluoric acid and ammonium fluoride) used in etching of SiO2, chemical solutions containing hydrochloric acid used in etching ITO, various acids (nitric acid, sulfuric acid, etc.) used in etching metal electrodes, and alkalis used in resist stripping solutions. (4) There are no internal or surface defects (bubbles, veins, inclusions, pits, scratches, etc.).
[0004] In addition to the above requirements, the following requirements (5) to (9) have also been made in recent years. (5) There is a demand for lighter weight displays and other products, and glass with a low specific gravity is desirable. (6) There is a demand for lighter weight displays and other products, and therefore thinner glass sheets are desirable. (7) In addition to the amorphous silicon (a-Si) type liquid crystal displays used up until now, polycrystalline silicon (p-Si) type liquid crystal displays, which require higher heat treatment temperatures, are now being manufactured (a-Si heat resistance: approximately 350°C, p-Si heat resistance: 350-550°C), making heat resistance desirable.
[0005] (8) Glass with a small average thermal expansion coefficient is required in order to increase productivity and thermal shock resistance by increasing the temperature rise and fall rate in heat treatment during the production of displays, etc. On the other hand, if the average thermal expansion coefficient of glass is too small, the glass will warp significantly when the number of film formation processes, such as gate metal films and gate insulating films, increases during the production of displays, etc., causing problems such as cracks and scratches during transportation of displays, and large deviations in exposure patterns. (9) Furthermore, in recent years, as glass substrates have become larger and thinner, there has been a demand for glass with a high specific elastic modulus (Young's modulus / density).
[0006] In order to satisfy the above-mentioned requirements, various glass compositions have been proposed so far, for example, for glass for display panels (see Patent Documents 1 to 4).
[0007] In recent years, electronic displays have been moving toward even higher resolution, and in large TVs, this has led to problems with substrate warpage due to the formation of various films, such as thicker Cu wiring, in line with the trend toward higher definition.Therefore, there is a growing need for substrates with less warpage, and in order to meet this need, it is necessary to increase the Young's modulus of glass. However, glasses with high Young's modulus as in Patent Documents 3 and 4 have high strain points and glass viscosities of 10 4 The devitrification temperature tends to be higher than the temperature T4 at which the glass becomes dPa s. As a result, it becomes difficult to mold the glass, and the burden on the manufacturing equipment increases, raising concerns about increased production costs. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent No. 5702888 [Patent Document 2] International Publication No. 2013 / 183626 [Patent Document 3] Japanese Patent No. 5849965 [Patent Document 4] Japanese Patent No. 5712922 Summary of the Invention [Problem to be solved by the invention]
[0009] The inventors of the present application further found the following concerns.
[0010] As described above, a high strain point or devitrification temperature makes it difficult to manufacture glass, but it has also been found that a high crystal growth rate is also a problem that makes glass manufacture difficult. That is, if the crystal growth rate is high, crystals precipitated during long-term production will be mixed into the manufactured glass and become foreign matter defects. Foreign matter defects mixed into glass, even if they are extremely small, may be the starting point for damage to the substrate when handling a large-sized substrate, for example, so it is important to reduce the crystal growth rate. The present inventors have found that there is no correlation between the crystal growth rate and the devitrification temperature, and the crystal growth rate is a characteristic independent of the devitrification temperature. Therefore, even if the devitrification temperature is low, it is difficult to obtain an alkali-free glass with high productivity and excellent quality if the crystal growth rate is high.
[0011] An object of the present invention is to provide a glass that can suppress deformation of a glass substrate, such as warping of the glass substrate, has excellent formability, imposes a low burden on production equipment, and further has a low crystal growth rate, resulting in excellent productivity and quality. [Means for solving the problem]
[0012] In order to achieve the above object, the present invention provides a composition in which the oxide-based mole percent is expressed as SiO2 63-75%, Al2O3 10-16%, B2O3 more than 0.5%, less than 5%, MgO 0.1-15%, CaO 0.1-12%, SrO 0-8%, Contains 0-6% BaO, [MgO] / [CaO] is greater than 1.5; The formula (A) is 1.131[SiO2]+1.933[Al2O3]+0.362[B2O3]+2.049[MgO]+1.751[CaO]+1.471[SrO]+1.039[BaO]-48.25, and the value of formula (A) is 82.5 or more. The formula (B) is 35.59[SiO2]+37.34[Al2O3]+24.59[B2O3]+31.13[MgO]+31.26[CaO]+30.78[SrO]+31.98[BaO]-2761, and the value of formula (B) is 690 or more and 800 or less. The formula (C) is -9.01[SiO2]+36.36[Al2O3]+5.7[B2O3]+5.13[MgO]+17.25[CaO]+7.65[SrO]+10.58[BaO], and the value of formula (C) is less than 100. The formula (D) is {-0.731[SiO2]+1.461[Al2O3]-0.157[B2O3]+1.904[MgO]+3.36[CaO]+3.411[SrO]+1.723[BaO]+(-3.318[MgO][CaO]-1.675[MgO][SrO]+1.757[MgO][BaO]+4.72[CaO][SrO]+2.094[CaO][BaO]+1.086[SrO][BaO])} / ([MgO]+[CaO]+[SrO]+[BaO]), and the value of formula (D) is 20 or less; Young's modulus is 83GPa or more, and the surface devitrification viscosity η c 10 4.2 The present invention provides an alkali-free glass (1) having a viscosity of dPa·s or more.
[0013] In the alkali-free glass (1) of the present invention, the formula (E) is 4.379[SiO2]+5.043[Al2O3]+4.805[B2O3]+4.828[MgO]+4.968[CaO]+5.051[SrO]+5.159[BaO]-453, and the value of the formula (E) is preferably 1.50 to 5.50.
[0014] The alkali-free glass (1) of the present invention preferably has a strain point of 690° C. or higher.
[0015] The alkali-free glass (1) of the present invention has a density of 2.8 g / cm 3 The average thermal expansion coefficient at 50 to 350°C is 30×10 -7 / ℃~45×10 -7 / °C is preferred.
[0016] The alkali-free glass (1) of the present invention has a glass viscosity of 10 2 The temperature T2 at which the glass viscosity becomes dPa·s is 1800°C or less, and the glass viscosity is 10 4 It is preferable that the temperature T4 at which the viscosity becomes dPa·s is 1400°C or lower.
[0017] The alkali-free glass (1) of the present invention preferably has an internal devitrification temperature of 1,320° C. or lower.
[0018] The alkali-free glass (1) of the present invention has an internal devitrification viscosity η d 10 4.4 dPa·s or higher is preferred.
[0019] The alkali-free glass (1) of the present invention preferably has a crystal growth rate of 100 μm / hr or less.
[0020] The alkali-free glass (1) of the present invention may contain at least one selected from the group consisting of Li2O, Na2O and K2O in a total amount of 0.2% or less, expressed in mole % on an oxide basis.
[0021] In addition, the present invention is expressed in mole percent based on oxides. SiO2 50-80%, Al2O3 8-20%, Li2O+Na2O+K2O 0~0.2%, P2O50-1%, [MgO] / [CaO] is more than 1.5, Young's modulus is 83GPa or more, Strain point is 690℃ or higher, Glass viscosity is 10 4 The temperature T4 at which the thermal expansion coefficient becomes dPa·s is 1400℃ or less. Glass viscosity is 10 2 The temperature T2 at which the thermal expansion coefficient becomes dPa·s is 1800°C or less. Internal devitrification temperature is 1320℃ or less, Internal devitrification viscosity η d 10 4.4 dPa s or more, Surface devitrification viscosity η c 10 4.2 dPa s or more, Crystal growth rate is 100μm / hr or less, Density is 2.8g / cm 3 below, Specific elastic modulus is 31 or more, The average thermal expansion coefficient at 50 to 350°C is 30×10 -7 / ℃~45×10 -7 / °C.
[0022] The alkali-free glass (2) of the present invention preferably contains 0 to 5% of B2O3, expressed in mole percent on an oxide basis.
[0023] The alkali-free glass (2) of the present invention preferably contains, in mole percent on an oxide basis, 0.1-15% MgO, 0.1-12% CaO, 0-8% SrO, and 0-6% BaO.
[0024] The alkali-free glass (2) of the present invention preferably contains, in mole percent on an oxide basis, 0-5% B2O3, 0.1-15% MgO, 0.1-12% CaO, 0-8% SrO, and 0-6% BaO.
[0025] In the alkali-free glass (2) of the present invention, the formula (A) is 1.131[SiO2]+1.933[Al2O3]+0.362[B2O3]+2.049[MgO]+1.751[CaO]+1.471[SrO]+1.039[BaO]-48.25, and the value of formula (A) is preferably 82.5 or more.
[0026] In the alkali-free glass (2) of the present invention, the formula (B) is 35.59[SiO2]+37.34[Al2O3]+24.59[B2O3]+31.13[MgO]+31.26[CaO]+30.78[SrO]+31.98[BaO]-2761, and the value of formula (B) is preferably 690 or more and 800 or less.
[0027] In the alkali-free glass (2) of the present invention, the formula (C) is −9.01[SiO2]+36.36[Al2O3]+5.7[B2O3]+5.13[MgO]+17.25[CaO]+7.65[SrO]+10.58[BaO], and the value of formula (C) is preferably 100 or less.
[0028] In the alkali-free glass (2) of the present invention, the formula (D) is {-0.731[SiO2]+1.461[Al2O3]-0.157[B2O3]+1.904[MgO]+3.36[CaO]+3.411[SrO]+1.723[BaO]+(-3.318[MgO][CaO]-1.675[MgO][SrO]+1.757[MgO][BaO]+4.72[CaO][SrO]+2.094[CaO][BaO]+1.086[SrO][BaO])} / ([MgO]+[CaO]+[SrO]+[BaO]), and the value of formula (D) is preferably 20 or less.
[0029] In the alkali-free glass (2) of the present invention, the formula (E) is 4.379[SiO2]+5.043[Al2O3]+4.805[B2O3]+4.828[MgO]+4.968[CaO]+5.051[SrO]+5.159[BaO]-453, and the value of the formula (E) is preferably 1.50 to 5.50.
[0030] The alkali-free glasses (1) and (2) of the present invention may contain F in an amount of 1.5 mol % or less.
[0031] The alkali-free glasses (1) and (2) of the present invention may contain up to 0.5% SnO2, expressed in mole percent on an oxide basis.
[0032] The alkali-free glasses (1) and (2) of the present invention may contain up to 0.09% ZrO2, expressed in mole percent on an oxide basis.
[0033] The alkali-free glasses (1) and (2) of the present invention have a β-OH value of 0.01 mm -1 Above 0.5mm -1 The following is preferred:
[0034] The alkali-free glasses (1) and (2) of the present invention preferably have an annealing point of 850° C. or lower.
[0035] The alkali-free glasses (1) and (2) of the present invention preferably have a compaction of 150 ppm or less before and after holding at 600° C. for 80 minutes.
[0036] The alkali-free glasses (1) and (2) of the present invention preferably have an equivalent cooling rate of 5° C. / min or more and 800° C. / min or less.
[0037] The alkali-free glasses (1) and (2) of the present invention preferably have a sludge volume of 30 ml or less during etching.
[0038] The alkali-free glasses (1) and (2) of the present invention preferably have a photoelastic constant of 31 nm / MPa / cm or less.
[0039] The glass plate containing the alkali-free glass (1) or (2) of the present invention is preferably a glass plate having at least one side of 2400 mm or more and a thickness of 1.0 mm or less.
[0040] The glass plate of the present invention is preferably produced by the float process or the fusion process.
[0041] The present invention also provides a display panel comprising the alkali-free glass (1) or (2) of the present invention.
[0042] The present invention also provides a semiconductor device comprising the alkali-free glass (1) or (2) of the present invention.
[0043] The present invention also provides an information recording medium comprising the alkali-free glass (1) or (2) of the present invention.
[0044] The present invention also provides a planar antenna comprising the alkali-free glass (1) or (2) of the present invention.
[0045] The present invention also provides a light-control laminate comprising the alkali-free glass (1) or (2) of the present invention.
[0046] The present invention also provides a vehicle window glass comprising the alkali-free glass (1) or (2) of the present invention.
[0047] The present invention also provides an acoustic diaphragm comprising the alkali-free glass (1) or (2) of the present invention. Effect of the Invention
[0048] The present invention can provide a glass that can suppress deformation of a glass substrate, such as warping of the glass substrate, has excellent formability, imposes a low burden on production equipment, and has a low crystal growth rate, resulting in further excellent productivity and quality. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0049] The alkali-free glass of the present invention will now be described. In the following, the composition range of each component of the glass is expressed in mole percent based on the oxide. However, the percentage of each component in formulas (A) to (E) is expressed as a mole percentage of each component calculated assuming that the total amount of the seven components, SiO2, Al2O3, B2O3, MgO, CaO, SrO, and BaO, is 100 mole %. In the following, the numerical range indicated as "numerical value A to numerical value B" indicates a range including numerical value A and numerical value B as the minimum and maximum values, respectively, and means numerical value A or more and numerical value B or less.
[0050] If the SiO2 content is less than 50 mol% (hereinafter simply referred to as %), the strain point does not rise sufficiently, and the average thermal expansion coefficient increases, tending to increase the specific gravity. Therefore, the SiO2 content is 50% or more, preferably 55% or more, preferably 60% or more, more preferably 63% or more, more preferably 64% or more, more preferably 65% or more, even more preferably 66% or more, particularly preferably 66.5% or more, and most preferably 67% or more. If the SiO2 content exceeds 80%, the melting property of the glass decreases, the Young's modulus decreases, and the devitrification temperature tends to increase. Therefore, the SiO2 content is 80% or less, preferably 75% or less, more preferably 74% or less, more preferably 73% or less, even more preferably 72% or less, particularly preferably 71.5% or less, and most preferably 71% or less.
[0051] Al2O3 increases Young's modulus to suppress deflection, suppresses phase separation of glass, and improves fracture toughness to increase glass strength. If the content of Al2O3 is less than 8%, these effects are unlikely to be achieved, and other components that increase the average thermal expansion coefficient are relatively increased, resulting in a tendency for the average thermal expansion coefficient to be large. Therefore, the content of Al2O3 is 8% or more, preferably 8.5% or more, more preferably 9% or more, more preferably 9.5% or more, even more preferably 10% or more, even more preferably 10.2% or more, even more preferably 10.4% or more, even more preferably 10.6% or more, particularly preferably 10.8% or more, particularly preferably 11% or more, especially preferably 11.2% or more, and most preferably 11.4% or more. If the content of Al2O3 exceeds 20%, the melting property of the glass may deteriorate, the strain point may increase, and the devitrification temperature may increase. Therefore, the content of Al2O3 is 20% or less, preferably 18% or less, preferably 17% or less, preferably 16.5% or less, more preferably 16% or less, more preferably 15.5% or less, more preferably 15% or less, even more preferably 14.7% or less, particularly preferably 14.5% or less, and most preferably 14.3% or less.
[0052] B2O3 improves the BHF resistance, improves the melting reactivity of glass, and lowers the devitrification temperature, so it can be contained in an amount of 5% or less. The content of B2O3 is preferably 4% or less, preferably 3.5% or less, preferably 3% or less, preferably 2.8% or less, more preferably 2.6% or less, even more preferably 2.5% or less, particularly preferably 2.4% or less, and most preferably 2.3% or less. In order to achieve the above-mentioned effects, the content of B2O3 is preferably more than 0.5%, more preferably 0.8% or more, even more preferably 1.2% or more, particularly preferably 1.5% or more, and most preferably 1.7% or more.
[0053] MgO can be added to increase the Young's modulus without increasing the specific gravity, thereby reducing the problem of deflection by increasing the specific elastic modulus, and to increase the fracture toughness value and glass strength. MgO also improves solubility. If the content of MgO is less than 0.1%, these effects are unlikely to be achieved, and the thermal expansion coefficient may become too low. Therefore, the content of MgO is preferably 0.1% or more. The content of MgO is more preferably 4% or more, more preferably 5% or more, more preferably 5.5% or more, even more preferably 6% or more, particularly preferably 6.2% or more, and most preferably 6.5% or more. However, if the MgO content is too high, the devitrification temperature is likely to rise, and therefore the MgO content is preferably 15% or less, more preferably 14% or less, more preferably 13% or less, more preferably 12% or less, more preferably 11.5% or less, still more preferably 11% or less, even more preferably 10.5% or less, particularly preferably 10% or less, and most preferably 9.5% or less.
[0054] CaO has the characteristic of increasing the specific elastic modulus next to MgO among alkaline earth metals and not excessively lowering the strain point, and also improves solubility like MgO. Furthermore, it can be contained because it has the characteristic of being less likely to increase the devitrification temperature than MgO. If the CaO content is less than 0.1%, these effects are less likely to appear. Therefore, the CaO content is preferably 0.1% or more. The CaO content is more preferably 3% or more, more preferably 3.5% or more, more preferably 4% or more, even more preferably 4.5% or more, particularly preferably 5% or more, particularly preferably 5.5% or more, particularly preferably 6% or more, and most preferably 7% or more. If the CaO content exceeds 12%, the average thermal expansion coefficient becomes too high, and the devitrification temperature becomes high, making devitrification a problem during glass production. Therefore, the CaO content is preferably 12% or less, more preferably 11% or less, more preferably 10% or less, even more preferably 9% or less, particularly preferably 8.5% or less, and most preferably 8% or less.
[0055] SrO can be contained in order to improve the melting property without increasing the devitrification temperature of the glass. The content of SrO is preferably 0.1% or more, more preferably 0.5% or more, further preferably 1% or more, particularly preferably 1.2% or more, and most preferably 1.3% or more. The above effects of SrO are lower than those of BaO, and if the amount of SrO is too large, the specific gravity becomes large and the average thermal expansion coefficient becomes too high. Therefore, the content of SrO is preferably 8% or less, more preferably 6% or less, even more preferably 5% or less, particularly preferably 4% or less, and most preferably 3% or less.
[0056] BaO can be contained in order to improve the melting property without increasing the devitrification temperature of the glass. The content of BaO is preferably 0.1% or more, more preferably 0.3% or more, further preferably 0.5% or more, particularly preferably 0.8% or more, and most preferably 1% or more. A large content of BaO tends to increase the specific gravity, decrease the Young's modulus, and increase the average thermal expansion coefficient too much. Therefore, the alkali-free glass of the present invention has a BaO content of preferably 6% or less, more preferably 5.5% or less, even more preferably 5% or less, particularly preferably 4.5% or less, and most preferably 4% or less.
[0057] Furthermore, the larger the blending ratio of MgO and CaO, [MgO] / [CaO], the higher the specific elastic modulus becomes. Increasing the specific elastic modulus (Young's modulus / density) of glass can prevent defects caused by bending of large and thin glass substrates in device manufacturing lines. For this reason, [MgO] / [CaO] is set to be greater than 1.5. [MgO] / [CaO] is preferably 1.8 or more, more preferably 2 or more, and even more preferably 2.5 or more. [MgO] / [CaO] is preferably 20 or less, more preferably 15 or less, and particularly preferably 10 or less. In addition, the expression "metal oxide" in the formula, such as [MgO], represents the mol % of the metal oxide component.
[0058] The alkali-free glass of the present invention does not substantially contain alkali metal oxides such as Li2O, Na2O, and K2O. In the present invention, "substantially does not contain alkali metal oxides" means that they are not contained except for inevitable impurities mixed from raw materials, that is, they are not intentionally contained. However, alkali metal oxides may be contained in a predetermined amount for the purpose of obtaining a specific action and effect (lowering the strain point, lowering Tg, lowering the annealing point, etc.). Specifically, at least one selected from the group consisting of Li2O, Na2O, and K2O may be contained in a total of 0.2% or less in mole % on an oxide basis. More preferably, it is 0.15% or less, more preferably 0.1% or less, more preferably 0.08% or less, even more preferably 0.05% or less, and most preferably 0.03% or less. At least one selected from the group consisting of Li2O, Na2O, and K2O may be contained in a total of 0.001% or more in mole % on an oxide basis.
[0059] In order to prevent deterioration of the characteristics of a thin film of metal or oxide provided on the surface of the glass plate when the alkali-free glass plate is used for display manufacturing, it is preferable that the alkali-free glass of the present invention does not substantially contain P2O5. In the present invention, "substantially not containing P2O5" means, for example, 1% or less, preferably 0.5% or less, and more preferably 0.1% or less. Furthermore, in order to facilitate recycling of glass and from the viewpoint of environmental load, it is preferable that the alkali-free glass of the present invention does not substantially contain PbO, As2O3, or Sb2O3. In the present invention, "substantially not containing PbO, As2O3, or Sb2O3" means that the contents of PbO, As2O3, and Sb2O3 are, for example, 0.01% or less, and preferably 0.005% or less, respectively.
[0060] On the other hand, in order to improve the meltability, clarity, formability, etc. of the glass, one or more of As2O3 and Sb2O3 may be contained in a total amount of 1% or less, preferably 0.5% or less, more preferably 0.3% or less, even more preferably 0.2% or less, even more preferably 0.15% or less, and even more preferably 0.1% or less.
[0061] In order to improve the melting property, clarity, formability, etc. of the glass, the alkali-free glass of the present invention may contain one or more of ZrO2, ZnO, Fe2O3, SO3, F, Cl, and SnO2 in a total amount of 2% or less, preferably 1% or less, and more preferably 0.5% or less. Among these, when F is contained to improve the melting property and clarity of glass, the F content is preferably 1.5% or less (0.43% by mass or less), more preferably 1% or less, even more preferably 0.5% or less, even more preferably 0.3% or less, even more preferably 0.1% or less, particularly preferably 0.05% or less, and most preferably 0.01% or less. Note that the F content is not the amount added in the glass raw material, but the amount remaining in the molten glass. This point is also the same for the Cl content described later. Among these, when SnO2 is contained to improve the melting property and clarification of the glass, the content of SnO2 is preferably 0.5% or less (1.1% by mass or less). ZrO2 may be contained in an amount of 0.001% or more (0.001% by mass or more) in order to lower the glass melting temperature, increase the Young's modulus, and improve the chemical resistance. However, if the ZrO2 content is too high, the devitrification temperature may be increased, the dielectric constant ε may be increased, and the glass may become non-uniform. In addition, when applied to a semiconductor device, there is a risk of causing failure due to α rays. The content of ZrO2 is preferably 0.09% or less (0.09% by mass or less), more preferably 0.08% or less (0.08% by mass or less), even more preferably 0.07% or less (0.07% by mass or less), even more preferably 0.06% or less (0.06% by mass or less), even more preferably 0.05% or less (0.05% by mass or less), even more preferably 0.04% or less (0.04% by mass or less), particularly preferably 0.03% or less (0.03% by mass or less), and most preferably substantially not contained. Substantially not containing ZrO2 means that it is not contained except for unavoidable impurities mixed in from raw materials, etc., that is, it is not intentionally contained.
[0062] In order to improve the meltability of the glass, Fe2O3 may be contained in an amount of 0.001% or more and 0.05% or less. If the iron content of the glass is reduced, Fe 2+ The amount of infrared absorption by the glass decreases, and as a result, the thermal conductivity of the glass increases. As a result, when glass is heated and melted by heat rays such as a burner flame in a glass melting furnace, the temperature distribution of the molten glass becomes small, the convection speed of the molten glass decreases, and the bubble quality and homogeneity of the glass product may deteriorate. Note that clarity and homogeneity depend on sufficient convection of the molten glass. When the amount of iron in the glass increases, the iron becomes Fe 2+ Or Fe 3+ This can reduce the transmittance of the glass. 3+has absorption in the wavelength range of 300 nm or less, which may reduce the ultraviolet transmittance of the glass. In order to obtain glass with a plate thickness of 0.5 mm and a transmittance of 20% or more at a wavelength of 300 nm, the Fe content (Fe2O3 equivalent) is preferably 0.05% or less, more preferably 0.04% or less, even more preferably 0.03% or less, still more preferably 0.02% or less, still more preferably 0.01% or less, still more preferably 0.008% or less, still more preferably 0.006% or less, still more preferably 0.004% or less, and particularly preferably 0.002% or less. On the other hand, when it is desired to improve the meltability of the glass, the Fe content (in terms of Fe2O3) is preferably 0.001% or more, more preferably 0.002% or more, even more preferably 0.005% or more, still more preferably 0.008% or more, still more preferably 0.01% or more, still more preferably 0.02% or more, still more preferably 0.03% or more, and particularly preferably 0.04% or more.
[0063] In order to improve the clarity of the glass, 0.1 to 1.0% of Cl may be contained. If the Cl content is less than 0.1%, the clarification effect during melting of the glass raw materials may be reduced. The Cl content is preferably 0.15% or more, more preferably 0.2% or more, further preferably 0.25% or more, and particularly preferably 0.3% or more. If the Cl content exceeds 1.0%, the effect of suppressing the growth of the bubble layer during glass production may decrease.The Cl content is preferably 0.8% or less, and more preferably 0.6% or less.
[0064] In order to improve the meltability, clarity, formability, etc. of the glass, to obtain absorption at a specific wavelength, and to improve density, hardness, bending rigidity, durability, etc., the alkali-free glass of the present invention may contain one or more of Se2O3, TeO2, Ga2O3, In2O3, GeO2, CdO, BeO, and Bi2O3 in a total amount of 2% or less, preferably 1% or less, more preferably 0.5% or less, even more preferably 0.3% or less, even more preferably 0.1% or less, particularly preferably 0.05% or less, and most preferably 0.01% or less. The GeO2 content is preferably less than 0.1%, more preferably 0.08% or less, even more preferably 0.05% or less, especially preferably 0.03% or less, most preferably 0.01% or less, and most preferably substantially not contained. "Substantially not containing GeO2" means that it is not contained except for unavoidable impurities mixed in from raw materials, etc., that is, it is not intentionally contained.
[0065] The alkali-free glass of the present invention may contain rare earth oxides and transition metal oxides in order to improve the melting property, clarity, formability, etc. of the glass and to improve the hardness, for example, Young's modulus, of the glass.
[0066] The alkali-free glass of the present invention may contain one or more of Sc2O3, Y2O3, La2O3, Ce2O3, CeO2, Pr2O3, Nd2O3, Pm2O3, Sm2O3, Eu2O3, Gd2O3, Tb2O3, Dy2O3, Ho2O3, Er2O3, Tm2O3, Yb2O3 and Lu2O3 in a total amount of 2% or less, preferably 1% or less, more preferably 0.5% or less, even more preferably 0.3% or less, even more preferably 0.1% or less, particularly preferably 0.05% or less, and most preferably 0.01% or less as rare earth oxides. The La2O3 content is preferably less than 1%, more preferably 0.5% or less, even more preferably 0.3% or less, particularly preferably 0.1% or less, most preferably 0.05% or less, and most preferably substantially none. "Substantially free of La2O3" means that La2O3 is not contained except as an unavoidable impurity mixed in from raw materials, etc., that is, it is not intentionally contained.
[0067] The alkali-free glass of the present invention may contain, as a transition metal oxide, one or more of V2O5, Ta2O3, Nb2O5, WO3, MoO3 and HfO2 in a total amount of 2% or less, preferably 1% or less, more preferably 0.5% or less, even more preferably 0.3% or less, still more preferably 0.1% or less, particularly preferably 0.05% or less, and most preferably 0.01% or less.
[0068] In order to improve the melting properties, etc. of the glass, the alkali-free glass of the present invention may contain ThO2, which is an actinide oxide, in an amount of 2% or less, preferably 1% or less, more preferably 0.5% or less, even more preferably 0.3% or less, still more preferably 0.1% or less, particularly preferably 0.05% or less, particularly preferably 0.01% or less, and most preferably 0.005% or less.
[0069] The alkali-free glass of the present invention has a β-OH value (mm -1 ) is 0.01 mm -1 Above 0.5mm -1 The following is preferred: The β-OH value is an index of the water content in glass. The absorbance of a glass sample is measured for light with wavelengths of 2.75 to 2.95 μm, and the maximum absorbance value β max is calculated by dividing by the thickness (mm) of the sample. -1 If the β-OH value is less than 0.45 mm, it is easy to achieve compaction at 600°C for 80 min, as described below. -1 Less than or equal to 0.4 mm is more preferable. -1 More preferably, it is 0.35 mm or less. -1 or less, and more preferably 0.3 mm -1 Less than 0.28 mm, more preferably -1 Less than 0.25 mm, more preferably -1 Less than 0.23 mm, more preferably -1 Less than 0.2 mm, more preferably -1 Less than 0.15 mm, more preferably -1 Less than 0.1 mm, more preferably -1 Less than 0.08 mm, particularly preferably 0.08 mm -1Less than 0.06mm, most preferably -1 On the other hand, the β-OH value is 0.01 mm -1 If the strain point of the glass described later is reached, the β-OH value is 0.05 mm or more. -1 More preferably, 0.08 mm or more is more preferable. -1 More than 0.1mm, preferably 0.1mm -1 More preferably, it is 0.13 mm or more. -1 More than 0.15 mm, particularly preferably -1 Above 0.18mm, most preferably 0.18mm -1 That's all.
[0070] The alkali-free glass of the present invention preferably has a value represented by the following formula (A) of 82.5 or more. 1.131[SiO2]+1.933[Al2O3]+0.362[B2O3]+2.049[MgO]+1.751[CaO]+1.471[SrO]+1.039[BaO]-48.25...Formula (A) The value represented by formula (A) is an index of the Young's modulus in the alkali-free glass of the present invention, and if this value is less than 82.5, the Young's modulus is likely to be low. In order to increase the Young's modulus in the alkali-free glass of the present invention, the value represented by formula (A) is preferably 83 or more, more preferably 83.5 or more, even more preferably 84 or more, particularly preferably 84.5 or more, and most preferably 85 or more.
[0071] The alkali-free glass of the present invention preferably has a value represented by the following formula (B) of 690 or more and 800 or less. 35.59[SiO2]+37.34[Al2O3]+24.59[B2O3]+31.13[MgO]+31.26[CaO]+30.78[SrO]+31.98[BaO]-2761···Formula (B) The value represented by formula (B) is an index of the strain point in the alkali-free glass of the present invention, and if this value exceeds 800, the strain point is likely to be high. If the value represented by formula (B) is 800 or less, the burden on the manufacturing equipment can be reduced. For example, the surface temperature of the roll used in forming the glass can be reduced, the life of the equipment can be extended, and productivity can be improved. In order to reduce the strain point in the alkali-free glass of the present invention, the value represented by formula (B) is more preferably 760 or less, even more preferably 750 or less, particularly preferably 745 or less, and most preferably 740 or less. If this value is less than 690, compaction may become too large, so the value is 690 or more. The value represented by formula (B) is preferably 695 or more, more preferably 700 or more, even more preferably 710 or more, particularly preferably 715 or more, even more preferably 720 or more, even more preferably 725 or more, and most preferably 730 or more.
[0072] In the alkali-free glass of the present invention, the value represented by the following formula (C) is preferably 100 or less. -9.01[SiO2]+36.36[Al2O3]+5.7[B2O3]+5.13[MgO]+17.25[CaO]+7.65[SrO]+10.58[BaO]...Formula (C) The value represented by formula (C) is an index of the crystal growth rate in the alkali-free glass of the present invention, and the crystal growth rate is low when this value is not more than 100. To reduce the crystal growth rate in the flow path of the molten glass in the alkali-free glass of the present invention, the value represented by formula (C) is more preferably not more than 95, even more preferably not more than 90, still more preferably not more than 85, particularly preferably not more than 80, and most preferably not more than 75. The inventors of the present application have found that there is no correlation between the crystal growth rate and the devitrification temperature, and the crystal growth rate is a property independent of the devitrification temperature. Even if the devitrification temperature of a glass is low, if the crystal growth rate is fast, it becomes difficult to obtain an alkali-free glass having excellent quality with high productivity.
[0073] In order to clean the surface or to reduce the thickness of a glass plate, the glass plate may be etched with an etching solution containing, for example, hydrofluoric acid (HF) (hereinafter, referred to as "etching process"). For this reason, the glass plate is required to have good processability during the etching process. In other words, the etching process speed must be within a practical range, the amount of sludge produced during the etching process must be small, and the sludge produced during the etching process must not easily gel. In the alkali-free glass of the present invention, the value represented by the following formula (D) is preferably 20 or less. {-0.731[SiO2]+1.461[Al2O3]-0.157[B2O3]+1.904[MgO]+3.36[CaO]+3.411[SrO]+1.723[BaO]+(-3.318[MgO][CaO]-1.675[ MgO][SrO]+1.757[MgO][BaO]+4.72[CaO][SrO]+2.094[CaO][BaO]+1.086[SrO][BaO])} / ([MgO]+[CaO]+[SrO]+[BaO])...Formula (D) The value represented by formula (D) is an index of the sludge volume during etching in the alkali-free glass of the present invention, and when this value is 20 or less, the sludge volume during, for example, hydrofluoric acid etching is small. Therefore, the sludge generated during etching is prevented from reattaching to the glass surface, the surface can be uniformly treated, and a glass product excellent in surface roughness and surface flatness can be obtained. In addition, a glass product excellent in surface cleanliness can be provided. The value represented by formula (D) is more preferably 18 or less, even more preferably 16 or less, even more preferably 15 or less, even more preferably 14 or less, even more preferably 13.5 or less, even more preferably 12 or less, even more preferably 11 or less, particularly preferably 10 or less, and most preferably 9 or less.
[0074] Glass sheets are sometimes etched for the purpose of cleaning the surface of the glass sheet or for the purpose of thinning the glass sheet. During the etching process, the glass is required to exhibit an appropriate etching rate. In the alkali-free glass of the present invention, the value represented by the following formula (E) is preferably from 1.50 to 5.50. 4.379[SiO2]+5.043[Al2O3]+4.805[B2O3]+4.828[MgO]+4.968[CaO]+5.051[SrO]+5.159[BaO]-453···Formula (E) The value represented by formula (E) is an index of the etching rate in the alkali-free glass of the present invention, and when this value is 1.50 or more, the etching rate is in a practical range. However, if the etching rate is too fast, it becomes difficult to control the etching process, and problems such as deterioration of the surface roughness of the glass plate may occur. If this value is 5.50 or less, such problems may not occur. The value represented by formula (E) is more preferably 1.90 or more, more preferably 2.00 or more, even more preferably 2.50 or more, even more preferably 3.00 or more, even more preferably 3.20 or more, even more preferably 3.50 or more, particularly preferably 4.00 or more, and most preferably 4.30 or more. The value represented by formula (E) is more preferably 5.00 or less, more preferably 4.80 or less, and even more preferably 4.60 or less.
[0075] The alkali-free glass of the present invention has a Young's modulus of 83 GPa or more. If the Young's modulus is within the above range, deformation of the substrate due to external stress is suppressed. For example, warping of the substrate can be suppressed when a film is formed on the surface of a glass substrate. As a specific example, warping of the substrate can be suppressed when a gate metal film such as copper or a gate insulating film such as silicon nitride is formed on the surface of the substrate in the manufacture of a TFT-side substrate of a flat panel display. In addition, for example, deflection when the size of the substrate is increased is also suppressed. In addition, damage to the substrate can be suppressed when the substrate with an increased size is handled. The Young's modulus is more preferably 83.5 GPa or more, more preferably 84 GPa or more, even more preferably 84.5 GPa or more, particularly preferably 85 GPa or more, and most preferably more than 85 GPa. In the alkali-free glass of the present invention, the Young's modulus can be measured by an ultrasonic method. The Young's modulus is preferably 115 GPa or less.
[0076] The alkali-free glass of the present invention preferably has a strain point of 690°C or higher. If the strain point is lower than 690°C, deformation of the glass plate and shrinkage (compaction) associated with stabilization of the glass structure are likely to occur when the glass plate is exposed to high temperatures in the thin film formation process of a display. The strain point is preferably 700°C or higher, more preferably 710°C or higher, even more preferably 720°C or higher, particularly preferably 725°C or higher, and most preferably 730°C or higher. On the other hand, if the strain point is too high, the temperature of the annealing device must be increased accordingly, and the life of the annealing device tends to decrease, so that a strain point of 800°C or lower is preferable. In addition, a lower strain point provides better formability of the glass. The strain point is preferably 780°C or lower, more preferably 760°C or lower, even more preferably 750°C or lower, particularly preferably 745°C or lower, and most preferably 740°C or lower.
[0077] The alkali-free glass of the present invention has a glass viscosity of 10 4 The temperature T4 at which the glass has a viscosity of dPa·s is preferably 1400°C or less. This provides excellent formability of the glass. In addition, for example, by lowering the temperature during glass forming, volatile matter in the atmosphere around the glass can be reduced, thereby reducing defects in the glass. Since glass can be formed at a low temperature, the burden on the manufacturing equipment can be reduced. For example, the life of equipment such as a float bath for forming glass can be extended, and productivity can be improved. T4 is preferably 1350°C or less, more preferably 1340°C or less, more preferably 1330°C or less, even more preferably 1320°C or less, even more preferably 1310°C or less, even more preferably 1300°C or less, even more preferably 1295°C or less, particularly preferably 1290°C or less, and most preferably 1285°C or less. T4 is measured using a rotational viscometer according to the method specified in ASTM C 965-96 (2017), and the viscosity is measured at 10 4 It can be calculated as the temperature at which the viscosity becomes dPa·s. In the examples described later, NBS710 and NIST717a were used as reference samples for calibrating the device.
[0078] The alkali-free glass of the present invention has a glass viscosity of 10 2The temperature T2 at which the glass melts is preferably 1800°C or less. By having T2 be 1800°C or less, the melting property of the glass is excellent and the burden on the manufacturing equipment can be reduced. For example, the life of equipment such as a kiln for melting glass can be extended, and productivity can be improved. In addition, defects derived from the kiln (for example, lumpy defects, Zr defects, etc.) can be reduced. T2 is more preferably 1770°C or less, more preferably 1750°C or less, even more preferably 1740°C or less, even more preferably 1730°C or less, even more preferably 1720°C or less, even more preferably 1710°C or less, even more preferably 1700°C or less, particularly preferably 1690°C or less, and most preferably 1680°C or less.
[0079] The alkali-free glass of the present invention preferably has an internal devitrification temperature of 1320°C or less. This provides excellent formability of the glass. It is possible to suppress the occurrence of crystals inside the glass during forming, which would result in a decrease in transmittance. It is also possible to reduce the burden on manufacturing equipment. For example, it is possible to extend the life of equipment such as float baths and fusion machines used to form the glass, thereby improving productivity. The internal devitrification temperature is more preferably 1310°C or lower, further preferably 1300°C or lower, further preferably 1280°C or lower, particularly preferably 1260°C or lower, and most preferably less than 1240°C. The internal devitrification temperature in the present invention can be determined as follows: crushed glass particles are placed in a platinum dish, heat-treated for 17 hours in an electric furnace controlled at a constant temperature, and after the heat treatment, an optical microscope is used to observe the maximum temperature at which crystals precipitate inside the glass and the minimum temperature at which crystals do not precipitate, and the average value is taken as the internal devitrification temperature.
[0080] The alkali-free glass of the present invention has an internal glass devitrification viscosity η d 10 4.4 This makes it difficult for foreign matter defects due to devitrification to occur during molding by the fusion method or float method. 4.5 dPa·s or more, more preferably 10 4.6 dPa·s or more, particularly preferably 10 4.7 dPa·s or more, most preferably 104.8 It is greater than or equal to dPa·s. The internal devitrification viscosity η in the present invention d That is, the internal glass devitrification temperature is obtained by the above-mentioned method, and the viscosity η of the glass at the internal glass devitrification temperature is measured to obtain the internal glass devitrification viscosity (η d ) is required.
[0081] The alkali-free glass of the present invention preferably has a surface devitrification temperature of 1370°C or less. This provides excellent formability of the glass. It is possible to suppress the occurrence of crystals inside the glass during forming, which would result in a decrease in transmittance. It is also possible to reduce the burden on manufacturing equipment. For example, it is possible to extend the life of equipment such as float baths and fusion machines used to form the glass, thereby improving productivity. The surface devitrification temperature is more preferably 1360°C or less, even more preferably 1350°C or less, even more preferably 1340°C or less, even more preferably 1330°C or less, even more preferably 1320°C or less, even more preferably 1310°C or less, even more preferably 1300°C or less, even more preferably 1290°C or less, particularly preferably 1280°C or less, and most preferably 1270°C or less. The surface devitrification temperature in the present invention can be determined as follows: crushed glass particles are placed in a platinum dish, heat-treated for 17 hours in an electric furnace controlled at a constant temperature, and after the heat treatment, the maximum temperature at which crystals precipitate on the glass surface and the minimum temperature at which no crystals precipitate are observed using an optical microscope, and the average value is taken as the surface devitrification temperature.
[0082] The alkali-free glass of the present invention has a glass surface devitrification viscosity η c 10 4.2 This makes it difficult for foreign matter defects due to devitrification to occur during molding by the fusion method or float method. 4.3 dPa·s or more, preferably 10 4.4 dPa·s or more, more preferably 10 4.5 dPa·s or more, particularly preferably 10 4.6 It is greater than or equal to dPa·s. Glass surface devitrification viscosity η in the present inventionc That is, the glass surface devitrification temperature is obtained by the above-mentioned method, and the glass viscosity η at the glass surface devitrification temperature is calculated. c The glass surface devitrification viscosity (η c ) is required.
[0083] The alkali-free glass of the present invention preferably has a crystal growth rate of 100 μm / hr or less. This can prevent the shortening of the life of the manufacturing equipment due to crystal precipitation in the flow path of the molten glass. In addition, the risk of the precipitated crystals being mixed into the manufactured glass and becoming a foreign matter defect is reduced. Note that, even if the foreign matter defects mixed into the glass are extremely small in size, they may become the starting point of damage to the substrate when handling a large-sized substrate, for example, a substrate with one side of 2400 mm or more, so it is important to reduce the crystal growth rate. The crystal growth rate in the present invention can be determined as follows. Specifically, crushed glass particles are placed in a platinum dish and heat-treated for 17 hours in an electric furnace controlled at a temperature close to the surface devitrification temperature to produce a number of primary crystal samples in which minute primary crystals are precipitated on the glass surface. The produced primary crystal samples are then cooled to a temperature of 100°C. 4 ~10 6 The glass is held at a temperature range where the viscosity of the glass is 10 dPa·s for 1 to 4 hours at 20°C intervals, and crystals are grown at each holding temperature. The longest part of the crystal grain is measured before and after holding at each holding temperature, the difference in crystal size before and after holding at each holding temperature is calculated, and the difference in crystal size is divided by the holding time to determine the crystal growth rate at each holding temperature. In the present invention, when the glass viscosity is 10 4 dPa·s~10 6 The maximum value of the growth rate in the temperature range where the crystal growth rate is dPa s is defined as the crystal growth rate. The crystal growth rate is more preferably 80 μm / hr or less, further preferably 65 μm / hr or less, particularly preferably 50 μm / hr or less, and most preferably 40 μm / hr or less.
[0084] The alkali-free glass of the present invention has a density of 2.8 g / cm 3The preferred density is 2.7 g / cm or less. This reduces the deflection caused by its own weight, making it easier to handle large substrates. It also reduces the weight of devices using glass. 3 Less than 2.68 g / cm is more preferable. 3 Less than 2.65 g / cm is more preferable. 3 Less than 2.63 g / cm is more preferable. 3 More preferably, 2.6 g / cm 3 It is particularly preferable that the size of the large substrate is less than 2400 mm.
[0085] The alkali-free glass of the present invention preferably has a specific elastic modulus (Young's modulus / density) of 31 or more. Increasing the specific elastic modulus (Young's modulus / density) of the glass can prevent defects caused by bending of large and thin glass substrates in device production lines. The specific elastic modulus (Young's modulus / density) of the glass is preferably 31.5 or more, more preferably 32 or more, even more preferably 32.2 or more, still more preferably 32.4 or more, still more preferably 32.6 or more, particularly preferably 32.8 or more, and most preferably 33 or more.
[0086] The alkali-free glass of the present invention has an average thermal expansion coefficient of 30×10 -7 / °C or more. The average thermal expansion coefficient at 50 to 350°C is 30×10 -7 If the temperature is less than 100°C, for example, in the manufacture of the TFT side substrate of a flat panel display, a gate metal film such as copper and a gate insulating film such as silicon nitride are sometimes laminated in that order on top of alkali-free glass, but the difference in thermal expansion between this and the gate metal film such as copper formed on the substrate surface will be large, which may cause problems such as warping of the substrate and peeling of the film. The average thermal expansion coefficient between 50 and 350°C is 33×10 -7 / ℃ or more is preferable, 35×10 -7 / ℃ or more is preferable, and 36×10 -7 / °C or more is more preferable, and 37×10 -7 / °C or higher, most preferably 38×10 -7 / ℃ or higher. On the other hand, the average thermal expansion coefficient at 50 to 350°C is 45×10 -7 If the temperature exceeds 45 × 10 / °C, the glass may break during the manufacturing process of products such as displays. -7 / °C or less is preferable. The average thermal expansion coefficient between 50 and 350°C is 43×10 -7 / ℃ or less is preferable, and 42×10 -7 / ℃ or less is more preferable, and 41.5×10 -7 / ℃ or less is more preferable, and 41×10 -7 / ℃ or less is more preferable, and 40.5×10 -7 / ℃ or less is particularly preferable, and 40.3×10 -7 / °C or less is most preferable.
[0087] The alkali-free glass of the present invention preferably has a compaction of 150 ppm or less before and after holding at 600°C for 80 minutes. Compaction is the thermal shrinkage rate of glass caused by relaxation of the glass structure during heat treatment. If the compaction is within the above range, it is possible to minimize the deformation of the glass and the dimensional change associated with the stabilization of the glass structure when exposed to high temperatures in the thin film formation process carried out in the manufacturing process of various displays. Compaction can be measured by the following procedure. A glass plate sample (a sample with a length of 100 mm, width of 10 mm, and thickness of 1 mm mirror-polished with cerium oxide) is held at a temperature of glass transition point +120°C for 5 minutes, and then cooled to room temperature at 40°C per minute. The total length (lengthwise direction) L1 of the sample is measured. Then, the sample is heated to 600°C at 100°C per hour, held at 600°C for 80 minutes, cooled to room temperature at 100°C per hour, and the total length L2 of the sample is measured again. The ratio (L1-L2) / L1 of the difference in the total length before and after the heat treatment at 600°C to the total length L1 of the sample before the heat treatment at 600°C is taken as the value of compaction. In the above evaluation method, compaction is more preferably 100 ppm or less, more preferably 90 ppm or less, even more preferably 80 ppm or less, even more preferably 75 ppm or less, particularly preferably 70 ppm or less, and most preferably 65 ppm or less. The absolute value of compaction is preferably close to 0 ppm. The smaller the absolute value of compaction, the less likely glass thermal shrinkage occurs, which is preferable.
[0088] In order to reduce compaction, the alkali-free glass of the present invention preferably has an equivalent cooling rate of, for example, 800°C / min or less. Here, the definition of the equivalent cooling rate and the evaluation method are as follows. Glass processed into a rectangular parallelepiped of 10 mm x 10 mm x 1 mm is held at the glass transition point +120°C for 5 minutes using an infrared heating electric furnace, and then the glass is cooled to room temperature (25°C). At this time, multiple glass samples are produced with cooling rates varying in the range of 1°C / min to 1000°C / min. The refractive index n of the d line (wavelength 587.6 nm) of these samples is measured using a precision refractometer KPR-2000 manufactured by Shimadzu Devices Corporation. d is measured by the V-block method. d By plotting against the logarithm of the cooling rate, n d Next, we obtain a calibration curve for the n of glass that is actually melted in an electric furnace, molded, and cooled. d is measured by the above-mentioned measurement method. d The corresponding cooling rate (referred to as an equivalent cooling rate in the present invention) can be obtained from the calibration curve. From the viewpoint of the balance between compaction and productivity, the equivalent cooling rate is preferably 5°C / min or more and 800°C / min or less. From the viewpoint of productivity, the equivalent cooling rate is more preferably 10°C / min or more, even more preferably 15°C / min or more, particularly preferably 20°C / min or more, and most preferably 25°C / min or more. From the viewpoint of compaction, the equivalent cooling rate is more preferably 500°C / min or less, more preferably 300°C / min or less, even more preferably 200°C / min or less, particularly preferably 150°C / min or less, and most preferably 100°C / min or less.
[0089] The alkali-free glass of the present invention preferably has a sludge volume of 30 ml or less during etching. When the sludge volume during etching is within the above range, the sludge generated during etching is prevented from reattaching to the glass surface, the surface can be uniformly treated, and a glass product excellent in surface roughness and surface flatness can be obtained. In addition, a glass product excellent in surface cleanliness can be provided. The sludge volume is more preferably 20 ml or less, more preferably 15 ml or less, even more preferably 12 ml or less, particularly preferably 10 ml or less, and most preferably 8 ml or less. The sludge volume during the etching treatment in the present invention can be determined as follows. The non-alkali glass substrate 1 with a size of 0.5 mmt cut to 20 mm x 30 mm is washed, dried, and then the mass is measured. An aqueous solution (chemical solution) adjusted to 5 mass% hydrofluoric acid and 2 mass% hydrochloric acid is placed in a Teflon (registered trademark) container, and the chemical solution is kept at 40°C using a thermostatic bath, and the entire non-alkali glass substrate 1 is immersed in the chemical solution to completely dissolve the non-alkali glass substrate 1. In order to compensate for the consumption of hydrofluoric acid due to etching, 1.8 ml of 50 mass% hydrofluoric acid is added to the chemical solution, and a new non-alkali glass substrate 2 with a size of 20 mm x 30 mm x 0.5 mmt is immersed in the chemical solution, and the new non-alkali glass substrate 2 is also completely dissolved. Furthermore, 1.8 ml of 50 mass% hydrofluoric acid is added to the chemical solution, and a new non-alkali glass substrate 3 with a size of 20 mm x 30 mm x 0.5 mmt is completely dissolved in the chemical solution using the same procedure. The chemical solution in which the non-alkali glass substrates were dissolved was stirred with a magnetic stirrer and held overnight (24 hours) to generate sludge, which is an insoluble matter, in the chemical solution. A Teflon (registered trademark) lid was placed on the container during the test to prevent evaporation of the chemical solution. The chemical solution and sludge in the Teflon (registered trademark) container were then transferred to a measuring cylinder, and after leaving the container for 24 hours to allow the sludge to settle, the volume of the sludge was measured using the graduations on the measuring cylinder, and this was taken as the sludge volume.
[0090] The alkali-free glass of the present invention preferably has an etching rate of 5.5 μm / min or less during etching. If the etching rate is too fast, it becomes difficult to control the etching process, and problems such as deterioration of the surface roughness of the glass sheet may occur. The etching rate is more preferably 5.0 μm / min or less, even more preferably 4.5 μm / min or less, particularly preferably 4.2 μm / min or less, and most preferably 4.0 μm / min or less. The etching rate during the etching process is preferably 2.40 μm / min or more. When the etching rate during the etching process is in the above range, the etching process speed is in a practical range. The etching rate during the etching process is more preferably 2.50 μm / min or more, even more preferably 2.70 μm / min or more, particularly preferably 2.90 μm / min or more, and most preferably 3.00 μm / min or more. The etching rate during the etching process in the present invention can be determined as follows. A 0.5 mmt alkali-free glass substrate cut into 20 mm x 30 mm is washed, dried, and then its mass is measured. An aqueous solution (chemical solution) adjusted to 5 mass% hydrofluoric acid and 2 mass% hydrochloric acid is placed in a Teflon (registered trademark) container, the chemical solution is kept at 40°C using a thermostatic bath, and the entire alkali-free glass substrate is immersed in the chemical solution for 20 minutes. After immersion, the alkali-free glass substrate is washed with pure water, dried, and then its mass is measured. The surface area is calculated from the sample dimensions, and the amount of mass loss is divided by the density, divided by the surface area, and then further divided by the immersion time to calculate the etching rate per unit time.
[0091] The alkali-free glass of the present invention preferably has an annealing point of 850°C or less. If the annealing point is 850°C or less, the burden on the manufacturing equipment can be reduced. For example, the surface temperature of the roll used in forming the glass can be lowered, the life of the equipment can be extended, and productivity can be improved. The annealing point is more preferably 820°C or less, more preferably 810°C or less, even more preferably 800°C or less, particularly preferably 790°C or less, and most preferably 780°C or less. The annealing point is preferably 700°C or more.
[0092] The alkali-free glass of the present invention preferably has a glass transition point of 850°C or less. If the glass transition point is 850°C or less, the burden on the manufacturing equipment can be reduced. For example, the surface temperature of the roll used in forming the glass can be lowered, the life of the equipment can be extended, and the productivity can be improved. The glass transition point is more preferably 820°C or less, more preferably 810°C or less, even more preferably 800°C or less, particularly preferably 790°C or less, and most preferably 780°C or less. The glass transition point is more preferably 690°C or more.
[0093] The alkali-free glass of the present invention preferably has a photoelastic constant of 31 nm / MPa / cm or less. Stress generated during the manufacturing process of a liquid crystal display panel or during use of a liquid crystal display device can cause the glass substrate to have birefringence, causing a black display to turn gray, and reducing the contrast of the liquid crystal display. If the photoelastic constant is 31 nm / MPa / cm or less, this phenomenon can be suppressed. The photoelastic constant is more preferably 30 nm / MPa / cm or less, even more preferably 29 nm / MPa / cm or less, even more preferably 28.5 nm / MPa / cm or less, and particularly preferably 28 nm / MPa / cm or less. Considering the ease of ensuring other physical properties, the photoelastic constant is preferably 23 nm / MPa / cm or more, and more preferably 25 nm / MPa / cm or more. The photoelastic constant can be measured by a disk compression method at a measurement wavelength of 546 nm.
[0094] The alkali-free glass of the present invention has a high Young's modulus, preferably 82.5 GPa or more, suppresses deformation of the substrate due to external stress, has a low crystal growth rate, and suppresses the inclusion of foreign matter that may cause damage to the substrate in the glass, making it suitable for use as a glass plate used as a large substrate. A large substrate is, for example, a glass plate with at least one side of 2400 mm or more, specifically, a glass plate with a long side of 2400 mm or more and a short side of 2000 mm or more. The alkali-free glass of the present invention is more preferably a glass plate having at least one side of 2400 mm or more, for example, a glass plate having a long side of 2400 mm or more and a short side of 2100 mm or more, more preferably a glass plate having at least one side of 3000 mm or more, for example, a glass plate having a long side of 3000 mm or more and a short side of 2800 mm or more, particularly preferably a glass plate having at least one side of 3200 mm or more, for example, a glass plate having a long side of 3200 mm or more and a short side of 2900 mm or more, and most preferably a glass plate having at least one side of 3300 mm or more, for example, a glass plate having a long side of 3300 mm or more and a short side of 2950 mm or more. The glass plate of the present invention is preferably 1.0 mm or less in thickness because weight reduction can be achieved. The alkali-free glass of the present invention is more preferably 0.7 mm or less in thickness, more preferably 0.65 mm or less, even more preferably 0.55 mm or less, even more preferably 0.45 mm or less, and most preferably 0.4 mm or less. The thickness can be 0.1 mm or less, or 0.05 mm or less. However, from the viewpoint of preventing deformation due to its own weight, the thickness is preferably 0.1 mm or more, more preferably 0.2 mm or more.
[0095] The glass plate containing the alkali-free glass of the present invention can be produced, for example, by the following procedure. The raw materials of the above components are mixed so as to have the target contents in the glass composition, which is then charged into a melting furnace and heated to 1500 to 1800° C. to melt the mixture to obtain molten glass. The resulting molten glass is formed into a glass ribbon of a predetermined thickness in a forming device, and the glass ribbon is slowly cooled and then cut to obtain a glass sheet. The alkali-free glass of the present invention can incorporate a manufacturing method for reducing compaction. Specifically, for example, the equivalent cooling rate is preferably 500°C / min or less. Here, the definition and evaluation method of the equivalent cooling rate are as follows. Glass processed into a rectangular parallelepiped of 10 mm x 10 mm x 1 mm is held at the glass transition point +120°C for 5 minutes using an infrared heating electric furnace, and then the glass is cooled to room temperature (25°C). At this time, multiple glass samples are produced with cooling rates changed in the range of 1°C / min to 1000°C / min. The refractive index n of the d line (wavelength 587.6 nm) of these samples is measured using a precision refractometer KPR-2000 manufactured by Shimadzu Devices Corporation. d is measured by the V-block method. d By plotting against the logarithm of the cooling rate, n d Next, we obtain a calibration curve for the n of glass actually manufactured through processes such as melting, forming, and cooling on a production line. d is measured by the above-mentioned measurement method. d The corresponding cooling rate (referred to as an equivalent cooling rate in the present invention) can be obtained from the calibration curve. The equivalent cooling rate during slow cooling of the glass ribbon is preferably 5° C. / min or more and 500° C. / min or less from the viewpoint of the balance between compaction and productivity, more preferably 10° C. / min or more and 300° C. / min or less, and even more preferably 15° C. / min or more and 100° C. / min or less.
[0096] In the present invention, it is preferable to form the molten glass into a glass sheet by a float method, a fusion method or the like.
[0097] Next, the display panel of the present invention will be described. The display panel of the present invention has the above-mentioned alkali-free glass of the present invention as a glass substrate. The display panel is not particularly limited as long as it has the alkali-free glass of the present invention, and may be various display panels such as a liquid crystal display panel, an organic EL display panel, and an LED (Light Emitting Diode) display panel. In various display panels, the glass substrate of the alkali-free glass of the present invention may have, for example, a driving circuit or a scanning circuit using a thin film transistor (TFT; Thin Film Transistor). Taking the case of a thin film transistor liquid crystal display (TFT-LCD) as an example, it has a display surface electrode substrate (array substrate) on whose surface a gate electrode line and a gate insulating oxide layer are formed, and further a pixel electrode is formed on the surface of the oxide layer, and a color filter substrate on whose surface a RGB color filter and a counter electrode are formed, and a cell is formed by sandwiching a liquid crystal material between the pair of array substrate and color filter substrate. In addition to such a cell, a liquid crystal display panel includes other elements such as peripheral circuits. In the liquid crystal display panel of the present invention, the alkali-free glass of the present invention is used for at least one of the pair of substrates constituting the cell.
[0098] Next, the semiconductor device of the present invention has the above-mentioned alkali-free glass of the present invention as a glass substrate. Specifically, for example, the alkali-free glass of the present invention is used as a glass substrate for image sensors such as MEMS, CMOS, CIS, etc. Also, the alkali-free glass of the present invention is used as a cover glass for a display device for projection use, for example, a cover glass for LCOS (Liquid Crystal on Silicon).
[0099] Next, the information recording medium of the present invention has the above-mentioned alkali-free glass of the present invention as a glass substrate. Specifically, for example, the alkali-free glass of the present invention is used as a glass substrate for a magnetic recording medium or an optical disk. The magnetic recording medium may be, for example, an energy-assisted magnetic recording medium or a perpendicular magnetic recording medium.
[0100] Next, the planar antenna of the present invention has the above-mentioned alkali-free glass of the present invention as a glass substrate. Specifically, the alkali-free glass of the present invention is used as a glass substrate for a planar liquid crystal antenna having a planar shape such as a liquid crystal antenna or a microstrip antenna (patch antenna) as an antenna with good directivity and reception sensitivity. The liquid crystal antenna is disclosed, for example, in International Publication No. 2018 / 016398. The patch antenna is disclosed, for example, in Japanese Patent Publication No. 2017-509266 and Japanese Patent Publication No. 2017-063255.
[0101] The alkali-free glass of the present invention can be used as, for example, an antenna installation substrate or a protective material for a flat antenna. The protective material can prevent deterioration of the antenna function caused by ultraviolet rays, moisture (water vapor), and water, and damage or destruction of the antenna function caused by mechanical contact. A flat antenna comprising the alkali-free glass of the present invention can prevent a decrease in radiation efficiency caused by alkali components, has a high Young's modulus and is therefore less susceptible to damage and destruction, making it suitable for use as an antenna for transmitting and receiving radio waves in high frequency bands. Radio waves in a high frequency band are, for example, radio waves in a high frequency band (e.g., 0.3 GHz to 300 GHz) such as microwaves and millimeter waves, and include radio waves in the high frequency band for the fifth generation mobile communication system (5G) (e.g., a frequency band of 3.6 to 29.5 GHz, which includes the 3.7 GHz band (3.6 to 4.2 GHz), the 4.5 GHz band (4.4 to 4.9 GHz), and the 28 GHz band (27.5 to 29.5 GHz)). Antennas capable of receiving radio waves in high frequency bands are disclosed in, for example, WO2019 / 026963 and WO2019 / 107514.
[0102] The light-control laminate of the present invention has the above-mentioned alkali-free glass of the present invention as a glass substrate. The light-control laminate is, for example, a light-control laminate (also called a light-control device or light-control glass) provided with a light-control functional material that controls the light transmission state by electrical control. The light-control laminate can block or open the user's field of vision and control the inflow of infrared rays by controlling the light transmission state, so it can be used as a partition material for an interior, a building material such as an exterior window, a screen for displaying images, and the like. The light-control laminate is disclosed, for example, in International Publication No. 2017 / 213191 and Japanese Patent Application Laid-Open No. 2017-90617.
[0103] The vehicle window glass of the present invention has the above-mentioned alkali-free glass of the present invention as a glass plate. As described above, the vehicle window glass having the alkali-free glass of the present invention can stably transmit and receive radio waves in a high-frequency frequency band and is resistant to damage and destruction, and is therefore suitable for use as a window glass for autonomous vehicles.
[0104] The acoustic diaphragm of the present invention has the above-mentioned alkali-free glass of the present invention as a glass substrate. The alkali-free glass of the present invention has a high Young's modulus and is suitable for acoustic use. The acoustic diaphragm is disclosed, for example, in WO2019 / 070007, WO2018 / 181626, and JP2019-68368A. EXAMPLES
[0105] Examples will be described below, but the present invention is not limited to these Examples In the following, Examples 1 to 5 and Examples 9 to 13 are Examples, and Examples 6 to 8 and Examples 14 to 16 are Comparative Examples. The raw materials of each component were mixed so that the glass composition would be the target composition (unit: mol%) shown in Examples 1 to 16, and melted in a platinum crucible at 1600°C for 1 hour. After melting, the molten liquid was poured onto a carbon plate and held at a temperature of (glass transition point + 30°C) for 60 minutes, and then cooled to room temperature (25°C) at 1°C per minute to obtain a plate-shaped glass. This was mirror-polished to obtain a glass plate, which was then subjected to various evaluations. The results are shown in Tables 1 and 2. In Tables 1 and 2, the values shown in parentheses are calculated or estimated values. In Tables 1 and 2, RO represents the total amount of alkaline earth metal oxides.
[0106] The methods for measuring each physical property are shown below. (Average thermal expansion coefficient) Measurements were performed using a differential thermal expansion meter (TMA) according to the method specified in JIS R3102 (1995). The measurement temperature range was from room temperature to 400°C or higher, and the average thermal expansion coefficient from 50 to 350°C was calculated in units of 10. -7 Expressed as / °C. (density) According to the method specified in JIS Z 8807 (2012), a glass block of approximately 20 g containing no bubbles was measured by the liquid weighing method.
[0107] (distortion point) The measurement was performed using the fiber stretching method according to the method specified in JIS R3103-2 (2001). (Annealing point) The measurement was performed using the fiber stretching method according to the method specified in JIS R3103-2 (2001). (glass transition temperature) The measurements were performed using the thermal expansion method according to the method specified in JIS R3103-3 (2001). (Young's Modulus) According to the method specified in JIS R 1602 (1995), glass having a thickness of 1.0 to 10 mm was measured by the ultrasonic pulse method.
[0108] (T2) The viscosity was measured using a rotational viscometer according to the method specified in ASTM C 965-96 (2017). 2 The temperature T2 (℃) at which the viscosity reached dPa·s was measured. (T4) The viscosity was measured using a rotational viscometer according to the method specified in ASTM C 965-96 (2017). 4 The temperature T4 (℃) at which the viscosity reached dPa·s was measured.
[0109] (Surface devitrification temperature T c ) The glass was crushed and classified using a test sieve so that the particle size was in the range of 2 to 4 mm. The obtained glass cullet was ultrasonically cleaned in isopropyl alcohol for 5 minutes, washed with ion-exchanged water, dried, placed in a platinum dish, and heat-treated for 17 hours in an electric furnace controlled at a constant temperature. The heat treatment temperature was set at 10°C intervals. After the heat treatment, the glass was removed from the platinum dish and observed under an optical microscope for the maximum temperature at which crystals precipitated on the surface of the glass and the minimum temperature at which no crystals precipitated. The maximum temperature at which crystals precipitate on the glass surface and the minimum temperature at which no crystals precipitate were each measured once. If it was difficult to determine whether crystals precipitated, the measurements were sometimes taken twice. The glass surface devitrification temperature (T c ) was decided. (Surface devitrification viscosity η c ) The glass surface devitrification temperature (T c ) and the glass surface devitrification temperature (T c The viscosity of the glass at the temperature was measured to obtain the glass surface devitrification viscosity (η c ) was sought.
[0110] (Internal devitrification temperature T d ) The glass was crushed and classified using a test sieve so that the particle size was in the range of 2 to 4 mm. The obtained glass cullet was ultrasonically cleaned in isopropyl alcohol for 5 minutes, washed with ion-exchanged water, dried, placed in a platinum dish, and heat-treated for 17 hours in an electric furnace controlled at a constant temperature. The heat treatment temperature was set at 10°C intervals. After the heat treatment, the glass was removed from the platinum dish and observed under an optical microscope for the maximum temperature at which crystals precipitated on the surface of the glass and the minimum temperature at which no crystals precipitated. The maximum temperature at which crystals precipitate inside the glass and the minimum temperature at which no crystals precipitate were each measured once. If it was difficult to determine whether crystals precipitated, the measurements were sometimes taken twice. The maximum temperature at which crystals precipitate inside the glass and the minimum temperature at which crystals do not precipitate are averaged to determine the internal devitrification temperature (T d ) was decided. (Internal devitrification viscosity η d ) The internal glass devitrification temperature (T d ) and the internal glass devitrification temperature (T d The viscosity of the glass at 100° C. was measured to obtain the internal devitrification viscosity (η d ) was sought.
[0111] (crystal growth rate) Crushed glass particles are placed in a platinum dish and heat-treated for 17 hours in an electric furnace controlled at a temperature close to the surface devitrification temperature to produce multiple primary crystal samples in which minute primary crystals are precipitated on the surface of the glass. The primary crystal samples produced are then cooled to a temperature of 100°C. 4 ~10 6 The temperature was kept at 20°C intervals for 1 to 4 hours within the range where the viscosity of the glass was 10 dPa·s, and crystals were allowed to grow at each holding temperature. The longest part of the crystal grain was measured before and after holding at each holding temperature, and the difference in crystal size before and after holding at each holding temperature was calculated. The difference in crystal size was divided by the holding time to determine the growth rate at each holding temperature. 4 ~10 6 The maximum value of the growth rate in the temperature range where the crystal growth rate is dPa·s was taken as the crystal growth rate.
[0112] (etching rate) The raw materials of each component were mixed to obtain the target composition shown in Tables 1 and 2, and melted and refined in an electric furnace to obtain an alkali-free glass base material. The alkali-free glass base material was mirror-polished and cut to a size of 20 mm x 30 mm to obtain an alkali-free glass substrate 1 with a thickness of 0.5 mm. The substrate was washed, dried, and then its mass was measured. An aqueous solution (chemical solution) adjusted to 5% by mass of hydrofluoric acid and 2% by mass of hydrochloric acid was placed in a Teflon (registered trademark) container, the chemical solution was kept at 40° C. using a thermostatic chamber, and the non-alkali glass substrate was immersed in the chemical solution for 20 minutes. After immersion, the non-alkali glass substrate was washed with pure water and dried, and then its mass was measured. The surface area was calculated from the sample dimensions, divided by the density, divided by the surface area, and then divided by the immersion time to calculate the etching rate per unit time. (Sludge volume) The non-alkali glass substrate 1 used in the calculation of the etching rate was again immersed in the chemical solution at 40°C, and the non-alkali glass substrate 1 was completely dissolved. In order to compensate for the consumption of hydrofluoric acid by etching, 1.8 ml of 50 mass% hydrofluoric acid was added to the above chemical solution, and a new non-alkali glass substrate 2 with a size of 20 mm x 30 mm x 0.5 mmt was immersed in the chemical solution, and the new non-alkali glass substrate 2 was also completely dissolved. Furthermore, 1.8 ml of 50 mass% hydrofluoric acid was added to the above chemical solution, and a new non-alkali glass substrate 3 with a size of 20 mm x 30 mm x 0.5 mmt was completely dissolved in the chemical solution in the same manner. After the non-alkali glass substrate 3 was dissolved, the chemical solution was kept for a day and a night (24 hours) while being stirred with a magnet stirrer, and sludge, which is an insoluble matter, was generated in the chemical solution. In addition, in order to prevent the chemical solution from evaporating, a Teflon (registered trademark) lid was placed during the test. Thereafter, the mixed chemical solution and sludge in the Teflon (registered trademark) container were transferred to a measuring cylinder, and after leaving the sludge to settle for 24 hours, the volume of the sludge was measured using the graduations on the measuring cylinder and this was recorded as the sludge volume. (Specific elastic modulus) The specific elastic modulus is calculated by dividing the Young's modulus obtained by the above procedure by the density.
[0113] [Table 1]
[0114] [Table 2]
[0115] Examples 1 to 5 and 9 to 13, in which the value of formula (A) was 82.5 or more, had a Young's modulus of 83 GPa or more. On the other hand, Examples 6 and 14, in which the value of formula (A) was less than 82.5, had a Young's modulus of less than 83 GPa. Examples 1 to 5 and Examples 9 to 13, in which the value of formula (B) was 690 or more and 800 or less, had a strain point of 690° C. or more. Examples 7 and 15, in which the value of formula (B) was less than 690, had a strain point of less than 690° C. The crystal growth rates were 100 μm / hr or less in Examples 1 to 5 and 9 to 13, in which the value of formula (C) was 100 or less. On the other hand, the crystal growth rates were over 100 μm / hr in Examples 8 and 16, in which the value of formula (C) was more than 100. The sludge volume was 30 ml or less in Examples 1 to 5 and Examples 9 to 13, in which the value of formula (D) was 20 or less. On the other hand, the sludge volume was more than 30 ml in Examples 8 and 16, in which the value of formula (D) was more than 20. Examples 1 to 5 and Examples 9 to 13 show the surface devitrification viscosity η c 10 4.2 The surface devitrification viscosity η c 10 4.2 It was less than dPa·s.
[0116] Although the present invention has been described in detail and with reference to specific embodiments, it will be apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the invention. This application is based on Japanese Patent Application No. 2019-20257 filed on February 7, 2019, Japanese Patent Application No. 2019-51570 filed on March 19, 2019, Japanese Patent Application No. 2019-141422 filed on July 31, 2019, Japanese Patent Application No. 2019-186805 filed on October 10, 2019, and Japanese Patent Application No. 2020-17692 filed on February 5, 2020, the contents of which are incorporated herein by reference. [Industrial Applicability]
[0117] The alkali-free glass of the present invention having the above-mentioned characteristics is suitable for applications such as display substrates, photomask substrates, electronic device support substrates, information recording media, flat antenna substrates, light control laminate substrates, vehicle window glass, and acoustic diaphragms.
Claims
1. Contains BaO, In mole percent based on oxide Yes 2 50-80%, <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> 8~220%、 B 2 O 3 1.2~4%、 BaO 1.7% or less, Li 2 O+1 2 O+K 2 O0~0.2%、 P 2 O 5 0~1%, [MgO] / [CaO] is greater than 1.5; Young's modulus is 83 GPa or more, The strain point is 690°C or higher. Glass viscosity is 10 4 Temperature T at which viscosity becomes dPa·s 4 is 1400°C or less, Glass viscosity is 10 2 Temperature T at which viscosity becomes dPa·s 2 is 1800℃ or less, Internal devitrification temperature is 1320°C or less, Internal devitrification viscosity η d is 10 4.4 dPa·s or more, Surface devitrification viscosity η c is 10 4.2 dPa·s or more, The crystal growth rate is 100 μm / hr or less. Density is 2.8 g / cm 3 below, Specific elastic modulus is 31 or more, The average thermal expansion coefficient at 50 to 350°C is 30 x 10 -7 / ℃~45×10 -7 / °C.
2. 2. The alkali-free glass according to claim 1, containing 0.1 to 15% MgO, expressed in mole percent on an oxide basis.
3. 3. The alkali-free glass according to claim 1, containing 0.1 to 12% CaO, expressed in mole percent on an oxide basis.
4. The alkali-free glass according to any one of claims 1 to 3, containing 0 to 8% SrO, expressed in mole percent on an oxide basis.
5. Formula (A) is 1.131 [SiO 2 ]+1.933[Al 2 O 3 ]+0.362[B 2 O 3 ] + 2.049 [MgO] + 1.751 [CaO] + 1.471 [SrO] + 1.039 [BaO] - 48.25, and the value of formula (A) is 82.5 or more. The alkali-free glass according to any one of claims 1 to 4.
6. Formula (B) is 35.59 [SiO 2 ]+37.34[Al 2 O 3 ]+24.59[B 2 O 3 ] + 31.13 [MgO] + 31.26 [CaO] + 30.78 [SrO] + 31.98 [BaO] - 2761, and the value of formula (B) is 690 or more and 800 or less. The alkali-free glass according to any one of claims 1 to 5.
7. Formula (C) is -9.01 [SiO 2 ]+36.36[Al 2 O 3 ]+5.7[B 2 O 3 ] + 5.13 [MgO] + 17.25 [CaO] + 7.65 [SrO] + 10.58 [BaO], and the value of formula (C) is 100 or less.
8. Formula (D) is -0.731 [SiO 2 ]+1.461[Al 2 O 3 ]−0.157[B 2 O 3 ] + 1.904 [MgO] + 3.36 [CaO] + 3.411 [SrO] + 1.723 [BaO] + (-3.318 [MgO] [CaO] - 1.675 [MgO] [SrO] + 1.757 [MgO] [BaO] + 4.72 [CaO] [SrO] + 2.094 [CaO] [BaO] + 1.086 [SrO] [BaO]) / ([MgO] + [CaO] + [SrO] + [BaO]), and the value of formula (D) is 20 or less. The alkali-free glass according to any one of claims 1 to 7.
9. Formula (E) is 4.379 [SiO 2 ]+5.043[Al 2 O 3 ]+4.805[B 2 O 3 ] + 4.828 [MgO] + 4.968 [CaO] + 5.051 [SrO] + 5.159 [BaO] - 453, and the value of formula (E) is 1.50 to 5.
50. The alkali-free glass according to any one of claims 1 to 8.
10. The alkali-free glass according to any one of claims 1 to 9, containing F in an amount of 1.5 mol% or less.
11. In terms of oxide mol%, SnO 2 The alkali-free glass according to any one of claims 1 to 10, containing 0.5% or less of
12. In terms of oxide mole percent, ZrO 2 The alkali-free glass according to any one of claims 1 to 11, containing 0.09% or less of
13. The β-OH value of the glass is 0.01 mm. -1 More than 0.5 mm -1 The alkali-free glass according to any one of claims 1 to 12, wherein:
14. The alkali-free glass according to any one of claims 1 to 13, having an annealing point of 850°C or lower.
15. The alkali-free glass according to any one of claims 1 to 14, which has a compaction of 150 ppm or less before and after holding at 600°C for 80 minutes.
16. The alkali-free glass according to any one of claims 1 to 15, having an equivalent cooling rate of 5°C / min or more and 800°C / min or less.
17. The alkali-free glass according to any one of claims 1 to 16, wherein a sludge volume during etching is 30 ml or less.
18. The alkali-free glass according to any one of claims 1 to 17, having a photoelastic constant of 31 nm / MPa / cm or less.
19. A glass plate comprising the alkali-free glass according to any one of claims 1 to 18, the glass plate having at least one side of 2400 mm or more and a thickness of 1.0 mm or less.
20. A display panel comprising the alkali-free glass according to any one of claims 1 to 18.
21. A semiconductor device comprising the alkali-free glass according to any one of claims 1 to 18.
22. An information recording medium comprising the alkali-free glass according to any one of claims 1 to 18.
23. A planar antenna comprising the alkali-free glass according to any one of claims 1 to 18.
24. A light-controlling laminate comprising the alkali-free glass according to any one of claims 1 to 18.
25. A vehicle window glass comprising the alkali-free glass according to any one of claims 1 to 18.
26. An acoustic diaphragm comprising the alkali-free glass according to any one of claims 1 to 18.
Citation Information
Patent Citations
Aluminosilicate glass not containing alkali, and its use
JP2000302475A
Glass substrate for flat panel display and production method thereof
JP2015083533A
Alkali-free glass
JP2016029001A
Production method of silicate glass, silicate glass, and silica raw material for silicate glass
JP2016113363A
Support glass substrate and laminate comprising the same
JP2016117641A